Presence of ectopic adrenocortical tissues in inguinoscrotal region suggests an association with undescended testis - Oezel, S. Kerem; Kazez, Ahmet; Akpolat, Nusret (Springer, 2007)
Ectopic adrenocortical tissues (EAT) are rare pathologies in children. They are frequently encountered in the inguinal region incidentally during surgical procedures but they are also classically known to be located from diaphragm to pelvis. EAT were investigated during inguinal procedures including inguinal hernia, hydrocele, hydrocele of cord and undescended testis (UDT) in 1,069 patients, 159 girls, 910 boys, from April 1997 until April 2006. All these nodules were confirmed to be adrenocortical tissues after histopathological examinations. Statistical analysis was done with Fisher's exact test. EAT were noted on the plexus pampiniformis external to processus vaginalis of 22 male patients (1.73%) during inguinal explorations. This figure was 1.63% for inguinal explorations of inguinal hernia, hydrocele and hydrocele of cord and 5.1% for UDT. This difference was statistically significant (P < 0.0001). There were no EAT detected during inguinal exploration of female patients. EAT are uncommon pathologies seen during inguinoscrotal explorations. Incidence of EAT is significantly increased with UDT. This increase may be explained with the embryological events that take place during adrenal and gonadal development. The relatively low observation of EAT in girls may be due to the localization of gonads and association of EAT with gonadal position. Adrenal rests in inguinal region may suggest an association with descent of gonads.
Keywords: ectopic adrenocortical tissue; child; undescended testis; gonadogenesis